in brief - Grigoryeva, Elena (project baikal, 2023)
We present an overview of cultural and architectural events of the first 4 months of 2023 held in Moscow and Irkutsk.
Keywords: Anatoly Byzov; Architectural Heritage Day; B2 Billiard Tournament; Vladimir Bukh; VI Plenum of the Board of the All-Russian Creative Professional Public Organisation “Union of Architects of Russia”; festivals; DNR